2022
DOI: 10.1039/d2sc04656c
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell RNA imaging using the CRISPR-dCas13 system with modified sgRNAs appended with fluorescent RNA aptamers

Abstract: The development of RNA imaging strategies in live cells is essential to improve our understanding of their role in various cellular functions. We report an efficient RNA imaging method based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Another modification to the sgRNA involves incorporating arrays of fluorescent RNA aptamers to amplify the signal in the dCas13/sgRNA/FP system, enabling simple and sensitive imaging and tracking of endogenous RNA. ( Tang et al, 2022 ).…”
Section: Fluorescent Signal Amplification Techniquesmentioning
confidence: 99%
“…Another modification to the sgRNA involves incorporating arrays of fluorescent RNA aptamers to amplify the signal in the dCas13/sgRNA/FP system, enabling simple and sensitive imaging and tracking of endogenous RNA. ( Tang et al, 2022 ).…”
Section: Fluorescent Signal Amplification Techniquesmentioning
confidence: 99%
“…Moreover, simultaneous imaging of multiple targets and multicolor imaging represent future directions for aptamer-based fluorescence imaging. In the context of multicolor imaging, fluorophores can consist of diverse orthogonal aptamer–ligand complexes, 46 fluorescent dyes conjugated to aptamers, 163 or nanomaterials serving as carriers. 23 Our research group has developed an intracellular RNA imaging method based on the CRISPR-dPspCas13b system ( Fig.…”
Section: Modalities Of Aptamer-based Molecular Imaging and Applicationsmentioning
confidence: 99%
“…A notable feature of the Pepper aptamer is that it can bind to eight different HBC dye analogs to give fluorescence emission across the visible spectrum, ranging from cyan to red . Although some studies have demonstrated the robustness of this aptamer in vitro and in eukaryotic cells, its activity in different bacteria remains largely unexplored. Only recently, a series of Pepper-based biosensors have been tested in E. coli .…”
Section: Introductionmentioning
confidence: 99%